PRMT5 and FOXP1 expression profile in invasive breast cancer patients undergoing neoadjuvant chemotherapy - Su, Hui; Liu, Yingxue; Zhang, Chunhong; Yu, Tao; Niu, Yingdong (Cellular and Molecular Biology, 2020)
Neoadjuvant chemotherapy is the standard treatment for patients with advanced localized breast cancer, but today it has found a good place in the early stages to achieve a negative surgical margin and increase the possibility of breast preservation. Numerous studies have shown that patient survival increases with a complete pathological response in the relationship of some immunological molecules known as immunohistochemistry markers. The aim of this study was to investigate the complete pathological response in the relationship between PRMT5 and FOXP1 expression. In a cross-sectional study of breast cancer patients in stages I to III, who were treated with Neoadjuvant chemotherapy at the Breast Cancer Research Institute during the years 2018 to 2019, were examined. A complete pathological response was obtained in cases where no tumors remained in the breast and axillary tissue after surgery. Immunohistochemical analyzes for FOXP1, PRMT5, and PR and ER biomarkers of the tumor were conducted. Data were analyzed using descriptive and analytical statistics by SPSS v. 21 software. 157 patients with a mean age of 47.5 ±16.2 years were included in the study. Our results revealed that there was no significant difference between the foxp1 Positive and Negative patients, in terms of cancer stage, metastasis, being PR or ER-positive (P>0.05). While being PRMT5+/- had a significant relationship with FOXP1 expression (p=0.001). In the case of the response to treatment, there was a significant association between a complete response and being foxp1 + (p=0.01). While in other immunohistochemistry markers, no significant association was found (P>0.05). Our study revealed no association of foxp1 and PRMT5 with other biomarkers of breast cancer and clinical progress of the disease. Our study revealed no association of foxp1 and PRMT5 with other biomarkers of breast cancer and clinical progress of the disease.